Pendekatan Matematika Realistik Berbantuan Blog terhadap Kemampuan Literasi Matematika - Ririn Anindya Putri; Yumira Simamora; Risna Mira Bella Saragih (Departement of Mathematics Education, 2023)
The goal of this research is to assess how students' mathematical literacy is affected by a realistic mathematics education approach supported by a media blog. Of the 90 students grade 7 Laboratories of MTs UINSU Medan as a population, a total of 68 students served as the sample. The sample consist of two classes, one class as the experimental class where RME was implemented, and the second class as the control class where conventional learning that is Direct Instruction was applied. The instrument used was a test of mathematical literacy skills in the form of a pre-test and a post-test in narrative form on Algebra material. The methodology used in this study is quantitative. Independent sample t-test in SPSS 25 is used to analyze the data. The findings indicated that compared to students who received traditional instruction (Direct Instruction), those who received RME-based instruction showed statistically significant gains in mathematical literacy (P-value 0.035<0.05).